Phase 4 studies in heart failure - What is done and what is needed? - Iyngkaran, P.; Liew, D.; McDonald, P.; Thomas, M.; Reid, Christopher; Chew, D.; Hare, D. (2016)
© 2016 Bentham Science Publishers.Congestive heart failure (CHF) therapeutics is generated through a well-described evidence generating process. Phases 1 - 3 of this process are required prior to approval and widespread clinical use. Phase 3 in almost all cases is a methodologically sound randomized controlled trial (RCT). After this phase it is generally accepted that the treatment has a significant, independent and prognostically beneficial effect on the pathophysiological process. A major criticism of RCTs is the population to whom the result is applicable. When this population is significantly different from the trial cohort the external validity comes into question. Should the continuation of the evidence generating process continue these problems might be identified. Post marketing surveillance through phase 4 and comparative effectiveness studies through phase 5 trials are often underperformed in comparison to the RCT. These processes can help identify remote adverse events and define new hypotheses for community level benefits. This review is aimed at exploring the post-marketing scene for CHF therapeutics from an Australian health system perspective. We explore the phases of clinical trials, the level of evidence currently available and options for ensuring greater accountability for community level CHF clinical outcomes.